The home as a system of practice and its implications for energy and water metabolism - Eon, C.; Breadsell, J.; Morrison, Greg; Byrne, Joshua (2018)
Policy and regulations for residential houses often consider the physical system alone and tend to focus on the energy performance of the building. This ignores the effect of occupants’ everyday practices and their interaction with the building technologies. This research applies practice theory and the concept of system of practice to eight Australian homes with the objectives of providing a deeper understanding of the complexities of the home system as w ell as providing approaches to enable (rather than persuade) resource reduction. The homes were investigated through explanatory design mixed methods which combined results of one year of longitudinal quantitative data collection and home occupant interviews. The results revealed that practices are performed in a sequential temporal spectrum as part of a routine and are influenced by interlocked practices as well as interlocking routines from other home occupants. Practices also follow established daily patterns reflected by a frequency distribution curve where the standard deviation reflects the degree of habituality of the practice. Highly interlocked practices with a high degree of habituality are challenging to affect. However, automation could enable resource intensive activities to be dis-interlocked from an established routine and make change within the home system of practice easier and more flexible.